Основні напрями соціальної роботи з дітьми з обмеженими можливостями: їх зміст та форми - Чернета, Світлана Юріївна; Cherneta, Svitlana Yu. (Fundacja „Oświata i nauka bez granic PRO FUTURO” Wyższa Szkoła Informatyki i Umiejętności (m. Łódź), 2016)
W artykule naukowym omawiane są podstawowe kierunki pracy socjalnej z dziećmi z niepełnosprawnością, ich treść, forma, jak również zidentyfikowano perspektywy wdrożenia metod innowacyjnych w pracy pracownika socjalnego z określoną grupą dzieci.In the scientific article analyzes the main directions of social work with children with disabilities: content and form analysis of prospects for the development of innovative methods in the work of a social worker with a certain category of children.У науковій статті проаналізовані основні напрями соціальної роботи з дітьми з обмеженими можливостями: їх зміст та форми та визначено перспективи впровадження інноваційних методик у роботі соціального працівника із визначеною категорією дітей. In the scientific article analyzes the main directions of social work with children with disabilities: content and form analysis of prospects for the development of innovative methods in the work of a social worker with a certain category of children.
Główne kierunki pracy socjalnej z dziećmi z niepełnosprawnością: ich treść i rodzaje
The main directions of social work with children with disabilities: content and form
Keywords: praca socjalna; dzieci z niepełnosprawnością; kierunki; treść; forma; metody innowacyjne; pracownik socjalny; соціальна робота; діти з обмеженими можливостями; напрями; зміст; форми; інноваційні методики; соціальний працівник; social work; children with disabilities; directions; content; forms; innovative methods; a social worker